Predictors of vaping intention among adolescents: a systematic review - Saruddin, Muhammad Zulhilmie; Abdul Manaf, Rosliza; Hamzah, Khadijahtul Qubra Amizah; Ahmad Khusairi, Ainaa Athirah (BioMed Central, 2025)
Background: Vaping behavior has risen sharply among adolescents, with intention to vape playing a significant role in initiating this practice. Adolescent experimentation with vapes remains a major public health concern. Identifying factors associated with vaping intention is essential for developing effective preventive measures before this risk behavior becomes established in adulthood. This systematic review aims to identify predictors of vaping intention among adolescents. Methods: The review follows the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) 2020 statement. A comprehensive literature search was conducted across four databases (PubMed, CINAHL, Scopus and Science Direct), focusing on original English-language articles published between 2017 and 2022. Studies were screened and analyzed systematically using content analysis approach to identify key predictors. Results: In total, 13 studies were included. Several potential predictors of vaping intention were identified, including sociodemographic, personality and psychological, social, environment and tobacco cognitive factors. Conclusions: Effective prevention programs should address these modifiable risk factors through multifaceted interventions that simultaneously target multiple predictors. Registration: This systematic review is registered to PROSPERO Registry (reference number: CRD42024552998).